Intelligent Framework for Web-Service Testing - L S RajivKrishna; Y Prasanth (International Journal of Advances in Applied Sciences, 2015)
Web services provides a distributed computing architecture, with an emerging way of service oriented architecture (SQA). Here service oriented architecture is an interface to both computer systems and web services. Which implements an interaction with each other in new and different ways. According to service oriented architecture it virtually provides a platform for web services to communicate with each other. As it was an easy way for communicating with both clients and services. Many organizations and companies are either evaluating themselves into an enterprise information architectures, or they are in the process of getting adopt to the web services technology. As web services are platform independent it is playing a major role in the enterprise environment, and currently web services are widely accepted by many companies and organizations. So commonly web services possess some challenges to the enterprise environment. As a part of it web service must be tested before publish into a service oriented architecture. It involves large number of test cases, test scenarios that takes more time and effort. Testing management is needed so that it should control the time effort and should reduce the complexity of web service in a large software system, also in a real time world. Automation testing faces these challenges and fixes these issues. Automation testing has an ability to handle the complexities which are experiencing by the web services in a current environment. This paper presents the automatic testing strategies of a web service and detect the problems between both manual and automation testing. Finally results shows the proper effective report on improving the visibility of testing process based on the web approach to enhance the critical communication among multiple testing groups.